2014
DOI: 10.1038/ejcn.2014.87
|View full text |Cite
|
Sign up to set email alerts
|

European children’s sugar intake on weekdays versus weekends: the IDEFICS study

Abstract: High intake of sugar remains an important nutritional problem in children of many European countries. Interventions aiming to prevent this diet pattern may optimize their impact by targeting dietary habits on Fridays and weekends. Furthermore, when conducting dietary assessment in children, data from weekends and Fridays in combination with a selection of Mondays to Thursdays are needed to capture habitual sugar intake. Age and dietary cultures should also be considered in dietary intervention and assessment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 22 publications
3
55
0
Order By: Relevance
“…Even though IDEFICS children tend to consume, for example, more sugar, sugar-rich foods and beverages during weekends compared with workdays, energy intake did not differ significantly between workdays and weekend days. 54 Still, slightly higher ED levels during weekends cannot be precluded, which may have led to a small underestimation of the present ED values.…”
mentioning
confidence: 72%
“…Even though IDEFICS children tend to consume, for example, more sugar, sugar-rich foods and beverages during weekends compared with workdays, energy intake did not differ significantly between workdays and weekend days. 54 Still, slightly higher ED levels during weekends cannot be precluded, which may have led to a small underestimation of the present ED values.…”
mentioning
confidence: 72%
“…Both categories of school meal participants (i.e., breakfast only and breakfast/lunch) had higher mean weekday HEI scores for milk and vegetables, and lower HEI scores for saturated fat and sodium compared to their HEI scores for weekend days [179]. Four out of seven international studies reported statistically significant findings with children displaying unhealthy dietary behaviors, such as increased sugar intake, during weekend days compared to weekdays [68, 113, 182, 183]. Three other international studies either found no difference [128, 184] or presented evidence showing favorable dietary behaviors during weekends compared to weekdays [185].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies investigating weekly variation in dietary intake and PA have generally found less healthy behaviour during the weekend. Larger intakes of total energy, fat, added sugar, different discretionary foods and alcohol have consistently been observed during the weekend in studies on Western populations (12)(13)(14)(15)(16)(17)43,(47)(48)(49)(50)(51)(52)(53)(54) . However, the increase in total energy intake during weekend days, compared with weekdays, observed in the present study was larger than demonstrated in other large-scale, national studies (13,(15)(16)(17) .…”
Section: Discussionmentioning
confidence: 95%